Evaluation of the compliance of provincial libraries in Luzon with the 1988 PLAI proposed minimum standards for public libraries - David, Sonia Lourdes L. 1967- (1998)
Among the salient findings of the study are: a) lack or more qualified staff to man the library; b) insufficient budget allocation for the library; c) weak print and non-print collection; d) inadequate facilities and equipment; e) limited library services and f) strong need to review library policies for more effective library administration.
Recommendations are formulated and are forwarded to the following concerned authorities and persons: 1. For the Local Government Officials, to see the importance of the public library in the community and thus appropriate reasonable budget for its maintenance and administration; 2. For the Librarians, to be active and to continue to pursue higher level of learnings so that they will not be left behind. It is also suggested that the librarians should take an active role in the profession by joining associations that will help them form ties with other librarians. 3. For the National Library, specifically the Public Libraries Division to take a second look at the standards for public libraries proposed ten years ago and make the necessary revisions called by the present times. More importantly, that it be finally strictly implemented so that our public librarians will be challenged to do something about their respective libraries. 4. For the legislators of our country, that they may be able to pass a law that will help modernize our public libraries all throughout the land and that one day make public libraries a significant part of the lives of every citizen of this nation.
The main objective of the study is to evaluate the extent of compliance of the provincial libraries in Luzon with the 1988 Proposed Minimum Standards for Public Libraries. It sought to find out the real status of the provincial libraries based from the standards. The different aspects that were focused upon were the following: 1) Staff; 2) Budget; 3) Collection; 4) Physical facilities and equipment; 5) Library services; 6) Library administration.
Computer print out.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: Public libraries -- Standards. -- Philippines -- Luzon; Public libraries -- Evaluation. -- Philippines -- Luzon